Mental health problems among transition-aged youth with physical disabilities: an initial evaluation - Amalfi, Amanda; Li, Jia Yin; Théberge-Lamoureux, Vanessa; Tang, Carmen; Rinaldi, Emilie; Khayargoli, Pranamika; Anaby, Dana (Frontiers in Rehabilitation Sciences, 2023)
Aim Decreased participation and complex transitions into adulthood among youth with disabilities may impede their well-being. To advance knowledge on the co-occurrence of mental health problems and physical disability, this brief report describes the frequency of mental health problems, measured by the Behavior Assessment System of Children (BASC-3), among transition-aged youth (14–25 years) with physical disabilities and examines the association between mental health problems and sex, age, and number of functional issues. Methods Thirty-three participants completed a demographic questionnaire and the BASC-3. Frequency of BASC-3 scales falling within 3 categories: “within norms”, “at risk”, and “clinically significant” were described. Crosstabs and Chi-square tests were used to examine the association between BASC-3 scales and sex, age (< and ≥ 20), and number of functional issues (< and ≥ 6). Results Overall, “somatization”, “self-esteem”, “depression” and “sense of inadequacy” were the most common subscales being at risk. Participants with a higher number of functional issues (≥6) were more likely to fall within “at risk” or “clinically significant” categories across 20 (out of 22) BASC-3 scales, and female participants tended to fall more within “at risk” or “clinically significant” categories for 8 of BASC-3 scales. Younger participants (<20) were ranked in the “at risk” or “clinically significant” categories for 7 scales. Conclusions Findings lend further support for the occurrence of mental health problems emerging in youth with physical disabilities and highlight initial trends especially across functional levels. Further investigation of such co-occurrences and the factors that affect their development is needed.